Volatility of aggregate volatility and hedge funds returns - Vikas Agarwal; Y. Eser Arisoy; Narayan Y. Naik (University of Cologne, Centre for Financial Research (CFR), 2015)
This paper investigates empirically whether uncertainty about volatility of the market portfolio can explain the performance of hedge funds both in the cross-section and over time. We measure uncertainty about volatility of the market portfolio via volatility of aggregate volatility (VOV) and construct an investable version of this measure by computing monthly returns on lookback straddles on the VIX index. We find that VOV exposure is a significant determinant of hedge fund returns at the overall index level, at different strategy levels, and at an individual fund level. After controlling for a large set of fund characteristics, we document a robust and significant negative risk premium for VOV exposure in the cross-section of hedge fund returns. We further show that strategies with less negative VOV betas outperform their counterparts during the financial crisis period when uncertainty was at its highest. On the contrary, strategies with more negative VOV betas generate superior returns when uncertainty in the market is less. Finally, we demonstrate that VOV exposure-return relationship of hedge funds is distinct from that of mutual funds and is consistent with the dynamic trading of hedge funds and risk-taking incentives arising from performance-based compensation of hedge funds.
Keywords: G10; G11; C13; 330; uncertainty; volatility of volatility; hedge funds; performance